语言的消亡 ：以新加坡潮州话为个案 : 兼论基本词汇的有阶分布 = Language decline : a case study on Singapore Teochew dialect and a study of the rank theory in basic word list - 何佩芩 Ho, Pei Qin (2009)
新加坡是个多语言、多方言的国家。徐大明，周清海和周松岑在《新加坡华社语言调查》指出方言除了在和祖父母沟通时使用率较高之外，在日常生活中使用的频率低，使用范围也萎缩。尽管在家中仍然保留方言的运用，但是方言将会逐渐被华语，英语或其他语言逐渐替代。在这个背景下，我们针对新加坡二十至三十岁的年轻人，以潮州话为中心，考察他们运用潮州话的口语能力。这项考察看似是个社会语言学意义上的研究，但实际上我们希望能够通过这次研究从侧面回答语言结构在语言逐步退化时所产生的变化。本文是针对潮州话的词汇系统的退化进行观察，采用的是以陈保亚(1995)提出的有阶核心词表为蓝图的基本词汇表。他指出相对于低阶的核心词汇，高阶的核心词汇比较稳固，不易于在语言接触中被所接触的语言所影响或替代。我们通过会说方言的各年龄层的人抽样调查以及录音，以经修改的陈保亚200个基本词汇为调查范围，进行诱导式的测试如图片和口头引导。Singapore is a country of multilingual and multi-dialects. According to Xu Daming, Chew Cheng Hai and Chen Songcen’s observation, apart from communicating to grandparents, dialects is losing its use as a medium of language and it is gradually replaced by Mandarin and English. As such, this paper focuses on the spoken ability in Teochew, particularly the lexical items, of young Singaporean Teochew speakers of age from 20 to 30. In order to show a falling trend of the dialect ability of Singapore Teochew speakers, we have also surveyed Singaporean Teochew speakers of various age groups. We have chosen Chen Baoya (1995) 200 fundamental word list as the basis of our lexical test. The list consists of 2 ranks of lexical items, with the higher rank of words being more cognate than the lower rank ones. It is hypothesized that the lexical items in the lower rank is more susceptible to borrowing in a case of language contact.